2002
DOI: 10.1292/jvms.64.855
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Chronic Wasting Disease in an Elk Imported to Korea from Canada.

Abstract: ABSTRACT. A seven-year-old male elk (Cervus elaphus nelsoni) was euthanized and necropsied after having a 3-week history of body weight loss, emaciation, excessive salivation, teeth grinding, fever, anorexia, and respiratory distress. The elk was imported into Korea from Canada on March 9, 1997. Gross pathologic findings were restricted to a diffuse fibrinous pneumonia. Microscopic lesions included mild neuronal vacuolation and spongiform change in the neuropil of selected brain stem nuclei and generalized ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
103
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 12 publications
0
103
0
2
Order By: Relevance
“…This disease was confirmed only in elk in the Republic of Korea in 2001, 2004 and 2005 [7,10]. Additional CWD cases were observed in red deer, sika deer, and crossbred sika and red deer in 2010 (unpublished data).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…This disease was confirmed only in elk in the Republic of Korea in 2001, 2004 and 2005 [7,10]. Additional CWD cases were observed in red deer, sika deer, and crossbred sika and red deer in 2010 (unpublished data).…”
mentioning
confidence: 86%
“…The polymorphism in Prnp at residue 132 was methionine/methionine (MM). Immunohistochemistry (IHC) was conducted as described previously, with minor modifications [10]. The primary antibody was monoclonal antibody F99/97.6.1 (VMRD, Pullman, WA, U.S.A.).…”
mentioning
confidence: 99%
“…Recently, it has been reported that elk imported from Canada to Korea were diagnosed with CWD (15). It is necessary for animal quarantine to include precautions for CWD.…”
Section: ) the Prpmentioning
confidence: 99%
“…Fortunately, CWD was not detected among the examined Japanese sika deer in this study (Table 3). CWD had been observed in the cervids that were imported to Korea (15). It has been reported that the first case of scrapie in Japan was observed in sheep that were imported from Canada (14).…”
Section: (Cervus Nippon Centralis and Cervus Nippon Yesoensis)mentioning
confidence: 99%
“…TSEs are characterized by abnormal prion proteins (PrP Sc ) acting as infectious agents, which are generated by posttranslational modification of normal prion proteins (PrP C ) that accumulate in the brain and lead to diseases [10,13]. No TSEs have been found in any animal species in the Republic of Korea except for CWD, which is known to have originated from imported elk from Canada [12]. National CWD surveillance has been conducted since 2001, and subsequent cases were found in farmed elk in 2004 and 2005 [6].…”
mentioning
confidence: 99%